OPTIMASI DISCOVERY LEARNING UNTUK MENINGKATKAN BERPIKIR KREATIF SISWA KELAS V PADA MATERI PERISTIWA ALAM - Nurfajriah, Silvia; Jayadinata, Asep Kurnia; Aeni, Ani Nur (Jurnal Pena Ilmiah, 2019)
Science education atithe elementary level is a subject related to natural phenomena that often occur in real life, in which some problems must be solved in learning. This study aims to see an increase in students' creative thinking abilities after the discovery learning models syapplied to natural event material. The method used in this study is the pre-experimental method with agresearch design using the design of the one group pretest-posttest design. The population in this study were all fifth-grade students of SDN 5 Kersamanah. The sample in this study was class V students. The instruments used were tests and non-tests. Test questions are questions about the test of creative thinking skills, while non-test questions include question aires, interviews, and observation of student activities. The conclusions that can be obtained from this study are the increase in the ability of creative thinking of high group students, middle group students, and low group students, as well as the existence of differences in the increase in creative thinking skills that exist in the three groups.